2014
DOI: 10.1002/lt.23811
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is a prognostic factor in living donor liver transplantation

Abstract: The aims of this study were to investigate sarcopenia as a novel predictor of mortality and sepsis after living donor liver transplantation (LDLT) and to evaluate the effects of early enteral nutrition on patients with sarcopenia. Two hundred four patients undergoing preoperative computed tomography within the month before LDLT were retrospectively evaluated. The lengths of the major and minor axes of the psoas muscle were simply measured at the caudal end of the third lumbar vertebra, and the area of the psoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
303
8
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 269 publications
(320 citation statements)
references
References 29 publications
5
303
8
4
Order By: Relevance
“…The prevalence greatly depended on the definition used. All studies that reported the prevalence of sarcopenia separately for males and females reported a higher prevalence among males (12,14,17,(21)(22)(23)(24)(25)(26)30).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence greatly depended on the definition used. All studies that reported the prevalence of sarcopenia separately for males and females reported a higher prevalence among males (12,14,17,(21)(22)(23)(24)(25)(26)30).…”
Section: Resultsmentioning
confidence: 99%
“…From these 28 records, eight studies assessed muscle mass with means other than CT and one study was performed in a population other than patients awaiting or undergoing liver transplantation. The remaining 19 studies, including 3803 patients in partly overlapping cohorts, were included in this systematic review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Cross-referencing yielded no additional records.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations